RANCANG BANGUN SISTEM INFORMASI MANAJEMEN ASET TETAP BERWUJUD (STUDI KASUS PT BRI DANAREKSA SEKURITAS) - Murti, Luis; Soetam Rizky Wicaksono (Pusat Riset dan Inovasi Nasional, 2022)
PT BRI Danareksa Sekuritas is a state-owned company engaged in investment that is trusted because this company is supervised by the Financial Services Authority (OJK) and also cooperates with the Indonesia Stock Exchange (IDX). The number of branches spread across various regions causes several problems in several branches related to the problem of integrating inventory data and the inventory process. The problem that arises is the inventory data that does not match the actual number of goods. In fact, often the data in excel does not or escapes to be updated. The difficulty that occurs is because PT BRI Danareksa Sekuritas has many branches, which still carry out data collection using excel manually. The development of a system carried out by the Three Major Phase method has three stages, namely analysis, design, and implementation. Based on these problems, this system was created to make it easier for companies to manage assets starting from making procurement, maintenance, borrowing, asset deletion and to making inventory reports in real time. The results of the research in the form of the implementation of a web-based Asset Management Information System Design at PT BRI Danareksa Sekuritas are expected to meet the company's needs in managing assets to be more effective and efficient.